HIV risk behaviors of male injecting drug users and associated non-condom use with regular female sexual partners in north-east India - Mishra, Ritu Kumar (BioMed Central, 2014)
BACKGROUND: In the context of increasing HIV prevalence among women in regular sexual partnerships, this paper examines the relationship between male injecting drug users' (IDUs) risky injecting practices and sexual risk behaviors with casual partners and inconsistent condom use with regular partners. METHODS: Data were drawn from the behavioral tracking survey, conducted in 2009 with 1,712 male IDUs in two districts each of Manipur and Nagaland states, in north-east India. IDUs' risky behaviors were determined using two measures: ever shared needles/syringes and engaged in unprotected sex with casual paid/unpaid female partners in the past 12 months. Inconsistent condom use with regular sexual partners (wife/girlfriend) in the past 12 months was assessed in terms of non-condom use in any sexual encounter. RESULTS: More than one-quarter of IDUs had shared needles/syringes, and 40% had a casual sexual partner. Among those who had casual sexual partners, 65% reported inconsistent condom use with such partners. IDUs who shared needles/syringes were more likely to engage in unprotected sex with their regular partners (95% vs 87%; adjusted OR = 2.31, 95% CI = 1.30–4.09). Similarly, IDUs who reported inconsistent condom use with casual partners were more likely to report unprotected sex with their regular partners (97% vs 66%; adjusted OR = 18.14, 95% CI = 6.82–48.21). CONCLUSION: IDUs who engage in risky injecting and/or sexual behaviors with casual partners also report non-condom use with their regular sex partners, suggesting the high likelihood of HIV transmission from IDUs to their regular sexual partners. Risk reduction programs for IDUs need to include communication about condom use in all relationships in an effort to achieve the goal of zero new infections.